Heat shock proteins in bacilli. - Streips, U N (1985)
Five strains of bacilli, including a nonsporulating strain, when heat shocked, accelerated the synthesis of a specific subset of proteins. The major heat shock protein in all bacilli had a molecular weight of 66,000. The response persisted for at least 40 min and could be eliminated upon a shift down to 37 degrees C.